China’s Growth Performance and Prospects - Yusuf, Shahid (China Studies Center, NU, 2018)
China has acquired enviable growth momentum, manufacturing capabilities are world class, STI system is improving, resource mobilization remains impressive, and trade competitiveness is strong. But ebbing globalization, structural changes, macroeconomic issues, the constraints imposed by corruption, pollution, and aging cloud growth prospects. Overseas commitments, military ambitions are a drain. A number of potential flashpoints increase the threat of conflict. Near term threats are from: domestic financial crisis that derails growth process with serious political consequences; a damaging trade war with the US that drags down global economy; disputes with neighbors and their allies that accidentally or otherwise lead to military action. All three are in the cards, which makes it difficult to claim that China’s economy will hum along as smoothly as it has done in the recent past.
Keywords: China; China’s economy